Neural Correlates of the Perception of Spoiled Food Stimuli - Becker, Christoph A.; Flaisch, Tobias; Renner, Britta; Schupp, Harald T. (Frontiers in Human Neuroscience, 2016)
The elicitation of disgust by the view of spoiled and rotten foods is considered as an adaptation preventing the ingestion of harmful microorganisms and pathogens. To provide an effective behavioral defense, inedible food items need to be detected automatically, i.e., in the absence of explicit processing goals, early in the processing stream, and triggering an alarm response, i.e., increased attentional capture. To examine these hypotheses, a set of stimulus material consisting of images of perishable foods (i.e., dairies, meats, fruits, and vegetables) at various stages of natural decay ranging from appetitive to disgusting was developed. In separate sessions, functional imaging and dense sensor event related potential data were collected while participants (N = 24) viewed the stimulus materials. Functional imaging data indicated larger activations in the extrastriate visual cortex during the processing of inedible as compared to edible food items. Furthermore, event-related potential recordings indicated that the processing of inedible food stimuli was associated with a relative positivity over inferior occipital sensor sites already at early stages of processing (< 200 ms), and subsequently, an increased late positive potential over parieto-occipital sensor regions. Taken together, these findings demonstrate the brain’s sensitivity to visual cues of foods that are spoiled or rotten.